Benchmarking the nutrition-related commitments and practices of major Belgian food companies - Iris Van Dam; Naomi Reimes; Stefanie Vandevijvere (BMC, 2022)
Abstract Background To benchmark and quantitatively assess the transparency, specificity and comprehensiveness of nutrition-related commitments, as well as related practices of the largest Belgian food companies. Methods The 'Business Impact Assessment on Obesity and population-level nutrition' (BIA-Obesity) was applied to evaluate nutrition-related commitments and practices concerning product formulation, labelling, promotion and accessibility by the biggest Belgian food and non-alcoholic beverage manufacturers (n = 19), supermarkets (n = 5) and quick-service restaurants (n = 7). Publicly available commitments were collected and company representatives given the opportunity to verify and complete the information (2019-2020). Commitments were scored according to the BIA-Obesity. To assess company practices, the following indicators were calculated: median Nutri-Score of product portfolios, the proportion of products not-permitted to be marketed to children (using the World Health Organisation Regional Office for Europe nutrient profile model), the proportion of ultra-processed food products (using the NOVA-classification) and the proportion of products displaying Nutri-Score on the front-of-pack. Promotions in supermarket flyers were analysed over a one-year period and quick-service restaurant density around schools was calculated. Correlations between commitments and performance indicators were calculated applying the Spearman's rank correlation coefficient. Results Eighteen out of 31 companies participated (56%). Overall BIA-Obesity scores for commitments ranged from 2 to 75% (median = 35%) with notable variation across policy domains and food industries. The proportion of portfolios consisting of A and B Nutri-Score products ranged from 0 to 100% (median = 29%). The median proportion of products not-permitted to be marketed to children was 81% (range = 12%-100%) and the median proportion of ultra-processed foods was 75% (range = 2%-100%) across product portfolios. No significant correlations were observed between the strength of commitments and related performance indicators. Conclusion Food industry actions do not meet recommended best practices. Performance indicators show large potential for improvement across policy domains and industries. Government regulations are urgently needed to improve food industry efforts and ensure that commitments translate into improved practices.